Assessing the public health impacts of legalizing recreational cannabis use in the USA. Issue 6 (17th April 2015) - Hall, W; Weier, M
<x xml:space="preserve">Abstract</x> A major challenge in assessing the public health impact of legalizing cannabis use in Colorado and Washington State is the absence of any experience with legal cannabis markets. The Netherlands created a de facto legalized cannabis market for recreational use, but policy analysts disagree about how it has affected rates of cannabis use. Some US states have created de facto legal supply of cannabis for medical use. So far this policy does not appear to have increased cannabis use or cannabis‐related harm. Given experience with more liberal alcohol policies, the legalization of recreational cannabis use is likely to increase use among current users. It is also likely that legalization will increase the number of new users among young adults but it remains uncertain how many may be recruited, within what time frame, among which groups within the population, and how many of these new users will become regular users.